PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR MELALUI PELATIHAN UMKM KERIPIK JAGUNG DI KAWASAN WISATA PANTAI TIHU KABUPATEN BOLAANG MONGONDOW - Desi Putri Dama; Rahmat Nasila; Tri Setiawati Maulana; Aulia Abdul Rahman (LPPM Universitas Bina Mandiri Gorontalo, 2025)
Economic empowerment of coastal communities is essential to support sustainable tourism and improve local welfare. Tihu Beach in Bolaang Mongondow Regency has strong tourism potential, yet MSME activities remain limited due to insufficient skills in product processing, packaging, and marketing. This community service program aimed to enhance community economic capacity through training and mentoring in producing corn chips as a local-based MSME product. A participatory approach with a one-group pretest–posttest design was applied to 15 participants. Activities included production training, food sanitation education, packaging assistance, and evaluation of knowledge and skills. The results indicated significant improvements across all training aspects, with the highest increase in packaging and labeling skills from 28 to 82. Economic analysis showed a potential net profit of approximately IDR 1,860,000 per month. The program supports skill development and the strengthening of tourism-based coastal MSMEs